DYNAMICS ANALYSIS OF 1D STRUCTURE INCLUDING RANDOM PARAMETER VIA FREQUENCY-DOMAIN STATE-VECTOR EQUATIONS - Machado, Marcela Rodrigues; Pereira, Vilson Souza; I. G. Costa, Dalmo; C. Moraes, Elson; Santos, José Maria Campos dos (Revista Interdisciplinar de Pesquisa em Engenharia, 2019)
The consideration of uncertainties in numerical models to obtain the probabilistic descriptions of dynamic response is becoming more desirable in the way to quantify the parametric and non-parametric uncertainties associated with the model. In this work, an alternative approach to the spectral element formulation, in which the exact wave solutions are not required, the spectral element matrix including random parameters is derived from the transfer matrix formulated directly from the frequency-domain state-vector equation of motion. The analyses were made to quantify the effect of uncertainty in the dynamic responses at high frequency bands and the Monte Carlo simulation is used to propagate the variation in dimensional properties of the structural parameters. Some interesting results are presented, showing the effects of uncertainty parameters in the dynamic response of the structure.